Exploring the Internet Usage for English Language Learning - Anne Suryani (Jurnal ILMU KOMUNIKASI, 2006)
Abstract: In this article, I discuss the idea about how Information and Communication Technologies – particularly the internet- can be developed as a tool to support independent learning. From my point of view, both new media and education are closely connected. Moreover, the internet has several functions that might be explored for academic purposes. Although there are some possibilities of using internet as a tool to learn English, it might not be easy to implement this idea in Indonesian universities because of various problems caused by cultural background, educational institution, government, community, also student’s and teacher’s perspectives. This paper explains these complexities in five parts: introduction; literature review; analysis; solutions; and conclusions which all are connected to the concepts of language, culture and identity.